Digital Darwinism Branding and Business Models in Jeopardy - Kreutzer, Ralf T.; Land, Karl-Heinz.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Copernicus, 2015)
Digital Darwinism is a key challenge for all companies and brands. Not all companies and managers are aware of the challenges lying ahead. This book helps to identify the need for change and adaption based on a framework of findings and additional tools to position you and your company in the digital rat race.
Why the Digital Revolution Is Challenging You and Why You Have to Act Now -- Digital Darwinism and the Social Revolution - Which Basic Needs of Man Represent the Fuel of the Revolution on the Part of the Customer -- Big Data and Technology - Drivers of the Information Revolution on the Part of the Company and Accelerators of the Era of Cooperation -- How the Social Revolution Is to Be Managed -- How Marketing Becomes the ROI Driver Within a Company -- Confidence - The New Currency in Marketing and Management -- Social CRM - The New Rules of the Game in Leading Customers -- Why Marketing Is Becoming a Service -- The Necessity of Change Management - Or Why Our Traditional Communication and Organizational Structures Are Becoming Obsolete.
Keywords: Economics; Science (General).; Marketing; Economics/Management Science; Marketing; Business Strategy/Leadership.; Popular Science, general